Preliminary Summary Of Proposed Plan (Tufts Archival Research Center, 2007)
Summary of proposed health care reform. Details coverage, corporate alliances, cost containment, revenue/funding sources, standard benefits, national administration, national health board, state responsibilities, health plans, health alliances, supplemental insurance, federal health insurance programs, and long term care. Addresses issues of administrative simplification, protecting underserved populations, malpractice, fraud and abuse, bankruptcy and anti-trust, healthcare workforce development, public health and prevention, and academic health centers and medical research. Provides tables illustrating national health expenditures and budgetary effects of health reform, as well as pictorial representation of health reform financing.